Empowering Farmers and Santri through Biomass Waste-Based Biochar Innovation as a Solution for Sustainable Agriculture and Green Economy in Samarinda - Ida Rosanti; Sri Endayani; Wita Nur Vadillah; Purbawati Purbawati; Hadi Safwan; Moh Amiruddin A. S. (Poltanesa, 2026)
This community service program conducted at Pesantren Rahmatullah and among local farmers in Samarinda introduces an innovative approach to biochar production using biomass waste. It aims to address critical agricultural issues such as land degradation, low soil fertility, climate change mitigation, and the promotion of sustainable green economy practices. Biochar is a carbon-rich material with a porous structure resulting from the pyrolysis of organic biomass waste such as wood and dry leaves. It plays a vital role in improving soil fertility, retaining nutrients and water, and supporting microbial life in the soil ecosystem. This program encompasses activities including field observation, socialization, hands-on workshops, mentoring, technology transfer, and evaluation, all designed to improve community knowledge and technical capacity in producing and applying biochar effectively. Pesantren Rahmatullah serves as a strategic educational and innovation hub, empowering local farmers through environmentally friendly agricultural practices. The outcomes of the program include improved agricultural productivity, reduced dependency on chemical fertilizers, the creation of biochar-based business opportunities, and enhanced environmental quality. The program ultimately positions the pesantren as a model for green economic transformation in Samarinda. The program ultimately positions the pesantren as a model for locally driven green economic transformation in Samarinda by promoting low-cost, environmentally friendly farming practices, reducing reliance on chemical fertilizers, and creating income-generating opportunities through biochar-based agro-industries using biomass waste.